Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1021/bi00219a005
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and conformational stability studies of Staphylococcus nuclease and its mutants, including the less stable nuclease-concanavalin A hybrids

Abstract: We report steady-state and time-resolved fluorescence studies with the single tryptophan protein, Staphylococcus aureus A, and several of its site-directed mutants. A couple of these mutants, nuclease-conA and nuclease-conA-S28G (which are hybrid proteins containing a six amino acid beta-turn substitute from concanavalin A), are found to have a much lower thermodynamic stability than the wild type. The thermal transition temperatures for nuclease-conA and S28G are 32.8 and 30.5 degrees C, which are about 20 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 26 publications
(29 reference statements)
9
46
0
Order By: Relevance
“…A comparison of these values with our values is summarized in Table 8. Eftink et al (1991) observed the unfolding of H124L at pH 7.2 using fluorimetry and obtained a value for AH,, smaller than ours by roughly the same factor as listed for V66L at the higher temperatures in Table 7.…”
Section: Discussionsupporting
confidence: 65%
“…A comparison of these values with our values is summarized in Table 8. Eftink et al (1991) observed the unfolding of H124L at pH 7.2 using fluorimetry and obtained a value for AH,, smaller than ours by roughly the same factor as listed for V66L at the higher temperatures in Table 7.…”
Section: Discussionsupporting
confidence: 65%
“…Biochemical Evidence for an H1/H4 Hydrophobic InterfaceThe predicted EF-hand pair in the Na V 1.5 COOH terminus contains a single tryptophan, Trp 1798 , which is important not only because our model predicts it to be integral to the hydrophobic interface but also because its intrinsic fluorescence can be used to probe and report the nature of the environment in which it is located (13,24,25). We thus prepared a GST fusion protein consisting of residues predicted to form the EF-hand pair (residues 1786 -1863) and carried out experiments using Trp 1798 as a reporter of its environment.…”
Section: Thermodynamic Cycle Analysis Is Consistent With Predictedmentioning
confidence: 99%
“…Our observation of significant destabilization by loop replacements is not unprecedented, however. Two Staphylococcus nuclease mutants constructed by replacing a fiveresidue 0-turn with a @-turn sequence from concanavalin A were found to be destabilized by about 4.5 kcal/mol with a corresponding reduction in T, of about 20 "C (Eftink et al, 1991). A mutant constructed by replacing the loop region of chymotrypsin inhibitor 2 with a nonapeptide sequence found in an a-helix in subtilisin Carlsberg is also significantly destabilized by about 8 kcal/mol (Osmark et al, 1993).…”
Section: Loop Swaps and Destabilizationmentioning
confidence: 99%